15-Hydroxyprostaglandin dehydrogenase inhibitor prevents contrast-induced acute kidney injury. Issue 1 (1st January 2021) - Kim, Byeong Woo; Kim, Hye Jung; Kim, Sun-Hee; Baik, Hyung Joo; Kang, Mi Seon; Kim, Dong-Hyun; Markowitz, Sanford D.; Kang, Sun Woo; Bae, Ki Beom
Abstract: The two primary mechanisms by which iodinated contrast media (CM) causes contrast-induced acute kidney injury (CIAKI) are the hemodynamic effect causing intrarenal vasoconstriction and the tubular toxic effect causing acute tubular necrosis. Inhibition of 15-hydroxyprostaglandin dehydrogenase (15-PGDH), which degrades prostaglandin E2 (PGE2), promotes tissue repair and regeneration in many organs. PGE2 causes intrarenal arterial vasodilation. In this study, we investigated whether a 15-PGDH inhibitor can act as a candidate for blocking these two major mechanisms of CIAKI. We established a CIAKI mouse model by injecting a 10 gram of iodine per body weight (gI/kg) dose of iodixanol into each mouse tail vein. A 15-PGDH inhibitor (SW033291), PGE1, or PGE2 were administered to compare the renal functional parameters, histologic injury, vasoconstriction, and renal blood flow changes. In addition, human renal proximal tubular epithelial cells were cultured in a CM-treated medium. SW033291, PGE1, or PGE2 were added to compare any changes in cell viability and apoptosis rate. CIAKI mice that received SW033291 had lower serum levels of creatinine, neutrophil gelatinase-associated lipocalin, and kidney injury molecule 1 ( p  < 0.001); lower histologic injury score and TUNEL positive rates ( p  < 0.001); and higher medullary arteriolar area ( p  < 0.05) and renal blood flow ( p  < 0.001) than CM + vehicle group. In cell culture experiments, Adding SW033291 increased the viability rate ( p  < 0.05) and decreased the apoptosis rate of the tubular epithelial cells ( p  < 0.001). This 15-PGDH inhibitor blocks the two primary mechanisms of CIAKI, intrarenal vasoconstriction and tubular cell toxicity, and thus has the potential to be a novel prophylaxis for CIAKI. Abbreviations: 15-PGDH: 15-hydroxyprostaglandin dehydrogenase; AMP: adenosine monophosphate; CIAKI: contrast-induced acute kidney injury; CM: contrast media; EP: prostaglandin E2 receptor; hRPTECs: human-derived renal proximal tubule epithelial cells; KIM-1: kidney injury molecule-1; MTT: 3-(4, 5-Dimethyl thiazol-2-yl)-2, 5-diphenyl tetrazolium bromide; NGAL: neutrophil gelatinase-associated lipocalin; PBS: phosphate-buffered saline; PGE1: prostaglandin E1 ; PGE2: prostaglandin E2 ; RBF: renal blood flow; TUNEL: terminal deoxynucleotidyl transferase-mediated dUTP nick-end labeling; α-SMA: α-Smooth muscle actin